Human resource management and public sector reforms: Trends and origins of a new approach - Roberto Passos Nogueira; José Paranaguá de Santana (Institute for Applied Economic Research (ipea), 2015)
This paper aims to show that public sector reforms, in the 1980s and 1990s, underemphasized the importance of human resource management, because, a) the reformers made strong emphasis on the need to reduce the size of the government apparatus; and, b) because they made war on state bureaucracy. The analysis shows that after two decades of reformist experiments, measures of correction are being taken in several countries to restore the importance of human resource management as public policy. But, in many places governments have lost their ability to regulate and govern owing to the combined effect of downsizing and underestimation of the human resource planning function. Governments are now endeavoring to rectify that strategic error, and a trend is emerging toward the upgrading of human resource management processes, which requires that some balance be sought between old and new ideas. Based on the classical study by Weber on bureaucracy, the authors understand that such balance could be found through human resource management if it is applied as a political function mediating between bureaucratic prerogatives and citizens' rights.
Keywords: 330